Burza mózgów w dydaktyce – (nie)potrzebny chaos - Cybulska-Wal, Alina (Dydaktyka Polonistyczna, 2016)
Research on brainstorming in school has demonstrated that almost all of the implemantations are done wrong because of the social and organisational errors. Alina Cybulska-Wal proposes to understand the main idea of brainstorming as the SOE triade: where Satisfaction, Organizing and Efficiency have an influence on each other. Sollutions mentioned in this article define what the problem of „brainstorming in school” is and help to run rewarding creative sessions.